Strategi Penanganan Guest Complaint Oleh Call Center di Holiday Inn Resort Baruna Bali - Widyadnyana, I Nyoman Ardy; Andiani, Nyoman Dini (Jurnal Mosaik Hospitaliti, 2025)
This research aims to identify and describe the call center strategy in guest complaints at Hotel Inn Resort Baruna Bali. The research subjects in this study were Call Center Staff, Supervisor, and Front office Manager. The data collection methods used in this research are observation, interview, and documentation study. The data was analyzed using qualitative methods. This study found that the strategy of handling guest complaints by the call center implemented at Holiday Inn Resort Baruna Bali Hotel is structured and focuses on guest satisfaction with a systematic, responsive, and empathetic approach. The process starts from listening carefully to the complaint, taking full responsibility, and giving a sincere apology. Next, appropriate solutions and alternative options are provided as per the guest's needs. If the issue cannot be resolved at the staff level, escalation to a higher management level is done to ensure optimal resolution. The hotel is also committed to providing transparent information and conducting follow-ups to ensure guest satisfaction once the complaint has been addressed.